(untitled) - Caroline Barnes (London, 1994)
This book contains 26 practical investigations which are suitable for use in the teaching of A Level Biology syllabuses and other related courses. These investigations are designed to both complement the biological content of these courses, and to allow the assessment of scientific skills
Keywords: plant physiology